Analysis of consumers' expectations and perceptions and evaluation of food safety standards along with regulatory frameworks for functional beverages containing botanicals - Jarunee Intrasook; Anal, Anil Kumar; Loc, Thai Nguyen; Tsusaka, Takuji W.; Royal Thai Government Fellowship; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Currently, reports on comprehensive food safety measures for functional beverages containing botanicals are rarely available. This study aims to assess both consumers{u2019} and food industry{u2019}s views on the safety of these products. These findings were then considered to propose a comprehensive food control system for functional beverages containing botanicals by comparative analysis of current measures in the European Union, Canada, Japan, the Republic of Korea, and Thailand. The study outputs are proposed for policy-based recommendations. Assessment of consumers{u2019} views of expectations and perceptions toward safety of these products was conducted to identify food safety gaps by using Food Safety Gap Scale (FSGS) model. The modified FSGS model based on relevant publications of food safety concerns on these products was analyzed by Confirmatory Factor Analysis, model fit indices, and construct reliability and validity, followed by the Importance-Performance Analysis to prioritize constructs for improvement. The survey with 470 respondents found that the modified FSGS model was reliable and valid. The result revealed that performances in commitment and regulation dimensions by competent authorities were highly prioritized. A clear policy direction, active communication, and specific regulations for functional beverages should be improved. Assessment dimension was found less prioritized while it is necessary to increase consumers{u2019} awareness, especially misunderstanding of safety of natural ingredients and overclaims on prevention of diseases or COVID-19 infection. The SWOT analysis using the Focus Group Discussion technique was performed with 19 participants from small, medium, and large enterprises. The outputs concluded that Thailand has potential to produce botanicals, while the food companies have capacities in the production for the global market. However, they are still facing many challenges in safety controls and commercialization such as inadequate and low-quality botanicals, limited knowledge in farmers, insufficient laboratory services, lack of specific regulations, and limitation of scientific information on safety and efficacy for human health. The food industry also faced strict inspection and inconsistent supplies of botanicals during the COVID-19 crisis. From the comparative study, the development of five measures for functional beverages containing botanicals was proposed under Thailand's perspective. For instance, the particular regulation converting requirements for botanicals, functional beverages, and function-related claims should be developed. In addition, political direction, adverse effect reporting system, laboratory services, and activities of communication and education should be strengthened. The recommendations for the entire food control system are helpful for policymakers to provide integrated management for food safety improvement.
A dissertation submitted in partial fulfillment of the requirements for the degree of doctor of Philosophy in Food Innovation, Nutrition, and Health
Thesis (Ph.D.) - Asian Institute of Technology, 2024
Keywords: Food safety; Consumers -- Attitudes; Functional foods